2015
DOI: 10.1097/qai.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

HIV Disease Progression in Seroconvertors from the CAPRISA 004 Tenofovir Gel Pre-exposure Prophylaxis Trial

Abstract: Background While antiretroviral pre-exposure prophylaxis (PrEP) prevents HIV acquisition, it is not known if it alters HIV disease progression. This study assesses whether tenofovir gel impacted on disease progression among CAPRISA 004 microbicide trial seroconvertors. Methods Eighty-three seroconvertors from the tenofovir and placebo gel arms of the CAPRISA 004 trial were monitored prospectively for a minimum two years by CD4 count and viral load (VL). Linear mixed models were fitted to HIV VL, and log rank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Interestingly, the presence of favorable alleles did not significantly impact disease progression in our sample set (25). Finally, as shown previously (39), being assigned to the TFV arm did not impact disease progression.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, the presence of favorable alleles did not significantly impact disease progression in our sample set (25). Finally, as shown previously (39), being assigned to the TFV arm did not impact disease progression.…”
Section: Resultssupporting
confidence: 77%
“…Finally, we found that viruses from the TFV arm were less infectious and replicated at rates similar to those of viruses from the placebo (PLB) arm. This is important, as women assigned to the TFV gel arm had higher VL set points than those in the PLB arm, which raised concern that the drug might have selected for fitter viral variants (39).…”
mentioning
confidence: 99%
“…Plasma and genital secretions collected by cervicovaginal lavages (CVLs) and/or Softcups were obtained from 13 women in the CAPRISA 002 and CAPRISA 004 cohorts, from Kwa-Zulu Natal, South Africa [33-35] (Supplementary Table 1). This study was approved by the Human Research Ethics Committees of the University of Witwatersrand, University of KwaZulu-Natal and University of Cape Town.…”
Section: Methodsmentioning
confidence: 99%
“…An additional concern relates to therapeutic success rates in patients with breakthrough infections following PrEP. Data from seroconvertors in CAPRISA 004 demonstrate no impact of topical antiretrovirals used as PrEP on disease progression [45] or therapeutic success rates. A separate concern about resistance is the use of the same drugs (eg.…”
Section: Existing Hiv Prevention Technologiesmentioning
confidence: 99%